Safety, cost and environmental impact of reprocessing high risk single-use medical devices: a systematic review and meta-analysis - McGrath, Niamh; Waldron, Catherine; Farragher, Ailish; Walsh, Cathal; Polisena, Julie (GMS Hygiene and Infection Control)
Aim: To estimate the safety, financial and environmental effects of reprocessing high risk SUMDs. Methods: Systematic review (PROSPERO ID: CRD42022365642) of primary trial and observational studies of human participants receiving reprocessed high risk SUMDs compared with first use of identical SUMDs. Reprocessing was defined as cleaning, disinfection, and sterilisation or related procedures, and function and safety testing. Items were sourced via database, grey literature and supplemental searching of English and German language sources. Included studies were quality appraised and primary outcomes (direct patient safety; indirect financial costs; environmental impacts) GRADE (Grade of Recommendation, Assessment, Development and Evaluation) assessed. Narrative synthesis and where feasible, meta-analysis were undertaken. Results: Ten studies (N=2,657 participants) examined two implantable (pacemaker, defibrillator) and three catheterisation (electrophysiology polyurethane, ablation and balloon) devices. Safety outcomes were available for both device types and cost outcomes were available for catheterisation devices. Except for one older study, there were no statistically significant differences in the odds of examined safety outcomes between new and once reprocessed SUMDs. Meta-analysis of catheterisation devices resulted in similar results (Infections: OR=0.67, 95% CI: 0.37–1.20, p=0.18; Battery depletion: OR=0.2.29, 95% CI: 0.83–6.31, p=0.11). One study of balloon catheterisation devices which accounted for indirect costs reported savings of CAN$ 129 per patient. The certainty of evidence, using the GRADE assessment, for each outcome was very low. Conclusion: We found no evidence of additional adverse safety outcomes for once reprocessed cardiac catheterisation or implantable cardiac SUMDs. However, our confidence that the same findings would be observed in future studies is very low. There was insufficient evidence to establish the cost-effectiveness or environmental impacts of reusing cardiac catheterisation or implantable SUMDs. High-quality randomised controlled trials, analyses of national device reprocessing surveillance systems, cost-effectiveness studies, and life cycle assessments are required in order to facilitate better comparison across devices and reprocessing contexts.